2021
DOI: 10.1161/jaha.120.019907
|View full text |Cite
|
Sign up to set email alerts
|

Racial and Ethnic Disparities in Management and Outcomes of Cardiac Arrest Complicating Acute Myocardial Infarction

Abstract: Background The role of race and ethnicity in the outcomes of cardiac arrest (CA) complicating acute myocardial infarction (AMI) is incompletely understood. Methods and Results This was a retrospective cohort study of adult admissions with AMI‐CA from the National Inpatient Sample (2012–2017). Self‐reported race/ethnicity was classified as White, Black, and others (Hispanic, Asian or Pacific Islander, Native American, Other). Outcomes of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…22 Demographic characteristics, hospital characteristics, acute organ failure, mechanical circulatory support, cardiac procedures, and noncardiac organ support use were identified for all admissions using previously used methodologies from our group. 23–39…”
Section: Methodsmentioning
confidence: 99%
“…22 Demographic characteristics, hospital characteristics, acute organ failure, mechanical circulatory support, cardiac procedures, and noncardiac organ support use were identified for all admissions using previously used methodologies from our group. 23–39…”
Section: Methodsmentioning
confidence: 99%
“…In the health care setting, structural racism manifests to perpetuate racial and ethnic disparities, seen in how often racial and ethnic minorities are not afforded life-saving care after cardiac arrest [55]. Furthermore, Black and Hispanic/Latino patients have significantly higher in-hospital mortality rates compared to White patients, even after controlling for socioeconomic status [56].…”
Section: Racism and Healthmentioning
confidence: 99%
“…We also found that Black patients were less likely to be treated by a surgical provider with long experience in the institution. Previous studies demonstrated unequal quantity and quality of procedural care between patients of different race in the United States: In patients undergoing thyroidectomy, most Black patients had a low-volume surgeon,48 and among patients with myocardial infarction, Black patients were less likely to undergo cardiac catheterization, coronary angioplasty, and coronary bypass surgery compared to White patients 49,50…”
Section: Discussionmentioning
confidence: 99%